A Roman Sarcophagus Depicting Scylla in the Çanakkale Troia Museum - Yaman, Hüseyin; Özhan, Tolga (Tekmeria, 2022)
This article discusses an inscribed sarcophagus that originates from Nikaia and is now on display in the Çanakkale Troia Museum. The front is divided into three framed panels. Each short end has a single frame, and both are decorated with a gorgoneion. On the front, pantomime masks occupy the left and right frames while the middle one is embellished with a bust depicting a young woman. This discussion focuses mainly on the identification of the relief in the central frame and the inscription on the sarcophagus. The middle figure arouses curiosity with her leafy garment and the steering oar that she carries on her shoulder, which is not a common image found in sarcophagus iconography. With her clothing, coiffure, posture and steering oar, it is argued that the relief represents Scylla because of its resemblance to a bronze bust of Scylla in the Cleveland Museum that is said to come from the Black Sea coast of Asia Minor. Scylla’s appearance on a sarcophagus has an apotropaic function. Aside from the steering oar, the Nikaian Scylla –as we choose to name her– is also reminiscent of terracotta protomes from Amisos, representing Amazons. The sarcophagus can be dated to the Hadrianic or early Antonine period.